Optimisation study and affecting mechanism of CaO/SiO2 and MgO on viscous behaviours of titanium-bearing blast furnace slag. (7th February 2020) - Liang, Haili; Chu, Mansheng; Feng, Cong; Tang, Jue; Liu, Zhenggen; Wang, Wanping
ABSTRACT: To improve the metallurgical properties of titanium-bearing blast furnace slag, the orthogonal test was carried out and analysed by the multi-index synthetic weighted scoring method. The optimal slag compositions of titanium-bearing BF slag were CaO/SiO2 1.25, MgO 12.00 wt-%, Al2 O3 11.00 wt-% and TiO2 10.00 wt-%. In addition, the CaO/SiO2 and MgO content had important effects on the break-point temperature, viscosity and activation energy of viscous flow. With an increasing CaO/SiO2 from 1.10 to 1.30, the break-point temperature increased, the slag viscosity and the activation energy of viscous flow decreased. As the MgO content grew from 6.00 to 12.00 wt-%, the viscosity decreased, while the break-point temperature and the activation energy of viscous flow first reduced and then increased. Besides, the deeply relevant mechanism was researched by Factsage 7.0, Fourier transform infrared spectroscopy and X-ray diffraction.